Orchestrating mathematical activities in the kindergarten: the role of inquiry - Carlsen, Martin (NOMAD Nordic Studies in Mathematics Education, 2010)
The aim of my study is to address the role played by inquiry in orchestrating a mathematical activity in the kindergarten. The study takes the inquiry cycle as a methodological departure, i.e. the whole process of designing, acting, observing, reflecting, and feeding back. The subtleties of how the kindergarten teachers and a didactician reason in order to orchestrate the mathematical activity and the role played by inquiry in this orchestration are hence analysed. The analyses show how inquiry in every phase of the inquiry cycle, plays a significant role in the orchestration of the mathematical activity. The participants become co-learners in these processes, and are involved in appropriating the mathematical tools and concepts as well as didactical issues involved in orchestrating a mathematical activity in the kindergarten.